Genetic substructure and complex demographic history of South African Bantu speakers - Dhriti Sengupta (Nature Portfolio, 2021)
Despite linguistic and geographic diversity in South Eastern Bantu-speaking (SEB) groups of South Africa, genetic variation in these groups has not been investigated in depth. Here, the authors analyse genome-wide data from 5056 individuals, providing insights into demographic history across SEB groups.